Sistem Pendukung Keputusan Pemilihan Pegawai Honorer Kelurahan Medan Sinembah Menerapkan Metode ROC dan MOORA - Ketrin Munthe; T Razeki Aditya Syahputra; Azi Alfisya Pasuli; Muhammad Andika Hasibuan (Bulletin of Informatics and Data Science, 2022)
An honorary employee is someone who works for a company that is eligible to be employed as a daily employee for a predetermined period of time and also with a definite salary from the company he works for. The problem experienced in this study is about the process of selecting honorary employees. The selection of honorary employees so far has only looked at education, even though in the process of selecting honorary employees several criteria must be used. The criteria in this study are Education, Age, Height, Distance from Home, Work Experience, Character and Test Values. From the problems encountered, it is very appropriate if the Medan Sinembah Village party implements a Decision Support System. The method used in this study is ROC and MOORA, this method was chosen because it is able to provide the best decision based on predetermined criteria where the best alternative is alternative A18 on behalf of "Andry" with a value of Yi = 0.328